THE DEVELOPMENT OF A STUDENT SURVEY ON ATTITUDES TOWARDS MATHEMATICS TEACHING-LEARNING PROCESSES - Mutohir, Toho Cholik; Lowrie, Tom; Patahuddin, Sitti Maesuri (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
This study aimed to develop a survey instrument to measure student attitudes towards mathematics teaching-learning processes that is appropriate for the Indonesian context. This study consisted of two phases: Phase 1 (n=320) was a pilot study to assess the suitability of the instrument items for Indonesian students. Phase 2 (n=1001) was conducted to examine the construct validity of the instrument. The data collected from Phase 1 were analysed using descriptive statistics (i.e., frequency counts, simple correlation, and one-way ANOVA for item analysis). Factor analysis was utilised to select items and for scale construction. The result of the screening process (44 items) was piloted to assess its reliability and validity. The instrument, consisting of 22 items, is a reliable and valid rating scale that measures three distinct factors: Teacher Presentation, Mathematics Interest, and Mathematics Value. The data from Phase 2 were analysed by employing confirmatory factor analysis (CFA) and the results confirmed that the three factors identified in the previous factor analysis underlie the student attitudes instrument.DOI: http://dx.doi.org/10.22342/jme.9.1.4193.1-14